Control of enzymatic browning in strawberry, apple, and pear by physical food preservation methods: comparing ultrasound and high-pressure inactivation of Polyphenoloxidase - Silva, Filipa Vinagre Marques; Sulaiman, Alifdalino (MDPI, 2022)
Polyphenoloxidase (PPO) enzyme can be found in fruits, vegetables and crustaceans. Its activity, promoted by oxygen, causes food browning with subsequent loss of quality and limited shelf life. Foods are pasteurized with conventional and novel physical methods to inactivate spoilage enzymes, thus avoiding the addition of unhealthy chemical preservatives. Ultrasound and high- pressure processing (HPP) are non-thermal technologies capable of retaining vitamins, bioactives and sensory components of fresh fruits. Enzyme residual activity vs. processing time were plotted for strawberry, apple, and pear purees subjected to thermosonication (1.3 W/g—71 °C), HPP-thermal (600 MPa—71 °C) and heat treatment alone at 71 °C. The PPO residual activities after treatments were highly variable. TS was the most effective for inactivating PPO, followed by thermal processing. HPP-thermal did not improve the inactivation compared with thermal treatment at 71 °C. The resistance of the three fruits’ PPOs exhibited the same pattern for the three technologies: pear PPO was the most resistant enzyme, followed by apple PPO and, lastly, strawberry PPO. However, the resistance of the three PPOs to TS was lower and very similar. Given the huge variability of PPO resistance, it is important to run inactivation tests for different fruits/cultivars. The results can assist manufacturers to avoid browning during processing, storage and distribution of fruit purees, juices and concentrates.